2019
DOI: 10.1007/s12110-019-09352-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Kin-Selection Theory Help to Explain Support Networks among Farmers in South-Central Ethiopia?

Abstract: Acknowledgements: This work was funded by a Leverhulme Trust Research Grant F/00182/BI. Part of the logistic support was provided by the Centre Français d'Etude Ethiopienne. We are particularly grateful to the people of the Hitoya and Tiyo districts, Arsi zone, Oromia region, for their warm welcome and for facilitating this research. We thank the field team for many months of hard work on the field on data collection. Suggestions provided by James Holland Jones, Aurelie Cailleau and Sid Karunaratne are greatly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Previous work in a similar community, focusing on the number of older brothers, has shown that later-born farmers were disadvantaged in agricultural productivity, marriage and reproductive success (Gibson and Gurmu 2011 ). Another study in a similar rural community has shown that last-born settled farmers have a significantly smaller kin network but tend to have an extended non-kin network compared with their brothers (Clech et al in press ). In addition, last-born sons might enjoy a different type of social capital compared with their older brothers as they might accumulate knowledge through the social networks of their older siblings, which potentially reduces the cost of labour migration for them.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in a similar community, focusing on the number of older brothers, has shown that later-born farmers were disadvantaged in agricultural productivity, marriage and reproductive success (Gibson and Gurmu 2011 ). Another study in a similar rural community has shown that last-born settled farmers have a significantly smaller kin network but tend to have an extended non-kin network compared with their brothers (Clech et al in press ). In addition, last-born sons might enjoy a different type of social capital compared with their older brothers as they might accumulate knowledge through the social networks of their older siblings, which potentially reduces the cost of labour migration for them.…”
Section: Discussionmentioning
confidence: 99%